Monitoring drylands: The MARAS system. (February 2019) - Oliva, Gabriel; Bran, Donaldo; Gaitán, Juan; Ferrante, Daniela; Massara, Virginia; Martínez, Guillermo García; Adema, Edgardo; Enrique, Mario; Domínguez, Erwin; Paredes, Paula
Abstract: MARAS (Monitoring of Arid and Semiarid Regions) consists of 379 ground monitors in Patagonia, a 624.500 km 2 semiarid area of southern Argentina and Chile. The objective of this paper was to describe the system and analyze four variables of the initial data base. Floristic composition, diversity and cover were analyzed with intercept lines (500 points). Patches (resource-sinks areas) and Interpatches (areas that loose resources) were described using Gap intercept lines (50 m). Eleven Landscape Functional Analysis indicators were recorded in 10 interpatches: Soil stability, Infiltration and Nutrient cycling. Vegetation Cover was 43 ± 2%, Richness 15 ± 7 species/monitor, Interpatch Size 154 ± 134 cm and LFA Stability Index 46 ± 1%. Cover, Richness and Stability maps had bimodal distribution and maximum in S and NE areas, following rainfall gradients. Variability analysis shows that cover estimations are within 5% error at site and regional scales. Graphical analysis of single monitors shows observational biases in interpatch size and LFA Stability index. Richness estimations correlate significantly with α diversity (R 2 = 0.80). Analysis of 5-year change in 115 monitors shows significant reductions in cover and interpatch length, especially N of the region. These base line evaluations enable analysis of future changes that were not possible with multiple techniques and isolated data bases. Highlights: 379 ground monitors of vegetation and soil were installed in Patagonia. Six teams in two countries shared a single protocol and data base. Errors of estimations at site and regional scales are acceptable. Contour maps of main variables show gradients associated to aridity. This baseline enables future change evaluation.